The Buddha party: how the people's Republic of China works to define and control Tibetan Buddhism - Powers, John (Oxford University Press, 2016)
Acts of ingratitude -- The limitations of propaganda -- Patriotic soul boys and other Chinese myths -- Tibetology with Chinese characteristics -- Chinese and Tibetan perspectives on history -- Tibetan spellings -- Chinese terms -- Buddhist terms